Skenaariotyöskentelyllä tietoa tulevaisuuden sosiaali- ja terveyspalveluista ja osaamistarpeista - Jauhiainen, Annikki; Sihvo, Päivi; Jääskeläinen, Heli; Ojasalo, Juuso; Hämäläinen, Susanne (Finnish Journal of eHealth and eWelfare, 2017)
The aim of the two development projects was to provide information about the future of digital social- and health care and the necessary future competencies. Data acquisition was carried out by scenario work in the future workshops. The workshops were attended total of 73 people. The participants worked in the social and health care, both in the public and private sectors, in ICT companies, in educational organizations, and in the third sector. Among the participants were also ordinary citizens. The workshops were remotely connected and data was collected into electronic bulletin boards. The workshops produced total of 25 scenarios, which found eight different themes: information management, quantified self, remote services, robotics - automation of manual labour, multiprofessionality, digital architecture, customer-oriented services and the customer's responsibility, and human encounter. Future competency consisted of ten areas of expertise, which classified into three broader categories: basic know-how of social and health care professionals, special know-how of social and health care professionals and the collective know-how of social and health care and technology professionals. The special know-how also includes information systems and software development skills. Scenario work provided preliminary information about the future social and health services and qualifications. This information will be used in further development projects of digital services as well as more widely in education planning. The future workshops provided information about the scenario method and its compatibility with development activities.